Impact of the SARS-CoV-2 pandemic on emergency surgery services: a multi-national survey among WSES members - Reichert, Martin; Sartelli, Massimo; Weigand, Markus A.; Doppstadt, Christoph; Hecker, Matthias; Reinisch-Liese, Alexander; Bender, Fabienne; Askevold, Ingolf Harald; Padberg, Winfried; Coccolini, Federico; Catena, Fausto; Hecker, Andreas (World journal of emergency surgery, 2020)
The SARS-CoV-2 pandemic is a major challenge for health care services worldwide. It’s impact on oncologic therapies and elective surgery has been described recently, and the literature provides guidelines regarding appropriate elective patient treatment during the pandemic. However, the impact of SARS-CoV-2 pandemic on emergency surgery services has been poorly investigated up to now.